Original and generic latanoprost for the treatment of glaucoma and ocular hypertension: Are they really the same?. (February 2015) - Golan, Shani; Rosenfeld, Eldar; Shemesh, Gabi; Kurtz, Shimon
Summary We compared the intraocular pressure (IOP)‐lowering effect and safety profile of latanoprost (Xalatan) with its generic variant, Glautan (Unipharm, Tel Aviv, Israel). After 1 and 4 weeks of treatment, a randomized, prospective, cross‐over comparison was carried out that included patients with open‐angle glaucoma or ocular hypertension, either naïve or treated and well‐controlled, who were attending the Department of Ophthalmology, Tel Aviv Medical Centre, Tel Aviv, Israel, between May 2010 and November 2012. After a 3‐week washout period for the medicated subjects, the participants were randomized to 4 weeks of treatment with either Xalatan or Glautan once every evening and then, after a 3‐week washout period, crossed‐over to the other treatment for an additional 4 weeks. Efficacy was expressed by a change in intraocular pressure at three designated hours of the day after 1 week and 1 month of treatment, and tolerability was determined by ocular side‐effects as reported by the patient in a questionnaire. A total of 19 patients (mean age at initial diagnosis 66 ± 9 years, 14 females) were enrolled, of whom 17 had bilateral open‐angle glaucoma and two had unilateral disease. Both drugs lowered intraocular pressure after 1 week and 1 month (P = 0.06 and P = 0.04, respectively) of treatment. Xalatan had a tendency of greater efficacy than Glautan both after 1 week and 1 month, but the difference was not statistically significant (P =0.69 and P = 0.34, respectively). Drug safety was similar for Xalatan or Glautan, but more ocular side‐effects were reported after treatment with Glautan (21 vs 12 for Xalatan, P = 0.06).